Psychedelic fungus (Psilocybe sp.) authentication in a case of illegal drug traffic: sporological, molecular analysis and identification of the psychoactive substance. Issue 1 (January 2019) - Solano, Jaime; Anabalón, Leonardo; Figueroa, Sylvia; Lizama, Cristian; Reyes, Luis Chávez; Gangitano, David
Abstract: In nature, there are >200 species of fungi with hallucinogenic properties. These fungi are classified as Psilocybe, Gymnopilus, and Panaeolus which contain active principles with hallucinogenic properties such as ibotenic acid, psilocybin, psilocin, or baeocystin. In Chile, fungi seizures are mainly of mature specimens or spores. However, clandestine laboratories have been found that process fungus samples at the mycelium stage. In this transient stage of growth (mycelium), traditional taxonomic identification is not feasible, making it necessary to develop a new method of study. Currently, DNA analysis is the only reliable method that can be used as an identification tool for the purposes of supporting evidence, due to the high variability of DNA between species. One way to identify the species of a distinctive DNA fragment is to study PCR products analyzed by real time PCR and sequencing. One of the most popular sequencing methods of forensic interest at the generic and intra-generic levels in plants is internal transcribed spacer (ITS). With real time PCR it is possible to distinguish PCR products by differential analysis of their melting temperature (Tm) curves. This paper describes morphological, chemical, and genetic analysis of mycelia of psychedelic fungi collected from a clandestine laboratory. The fungus species were identified using scanning electron microscopy (SEM), mass spectrometry, HRM analysis, and ITS sequencing. The sporological studies showed a generally smooth surface and oval shape, with maximum length 10.1 μm and width 6.4 μm. The alkaloid Psilocyn was identified by mass spectrometry, while HRM analysis and ITS sequencing identified the species as Psilocybe cubensis . A genetic match was confirmed between the HRM curves obtained from the mycelia (evidence) and biological tissue extracted from the fruiting bodies. Mycelia recovered from the evidence and fruiting bodies (control) were genetically indistinguishable. Highlights: The smooth showed surface and oval shape, with length 10.1 μm and width 6.4 μm. The alkaloid Psilocyn was identified by mass spectrometry. HRM analysis and ITS sequencing identified the species as Psilocybe cubensis . Mycelia and fruiting bodies were genetically indistinguishable.